ANALISIS YURIDIS PELAKSANAAN JUAL BELI HAK GUNA BANGUNAN YANG HAKNYA TELAH BERAKHIR DIATAS HAK PENGELOLAAN NOMOR 1/PETISAH TENGAH YANG TERDAFTAR PADA PEMERINTAH KOTA MEDAN - KARTINI ELISABET PURBA (PREMISE LAW JURNAL, 2014)
ABSTRACT The expired right to build cannot be transferred through a sale and purchase activity before the right is extended or renewed. The status of the building built on the land with right to build under the management right Number 1/Petisah will be returned to the City Government of Medan, the holder of management right, after the expiration of its right. The trading of the expired right to build on the management right is not a violation of the law, because, basically, a plot of land whose right is expired and the building built on it will return to the  state in this case the City Government of Medan as the holder of its management right and the right is not registered anymore in the Land Boardas the right to land untill it is given a new right. The recommendation to transfer right through trading is an absolute requirement of the management right holder for the expired right which needs to be considered by the parties and Notary to avoid the acts inflicting loss to one of the parties. Keywords: Juridical Analysis, Building Trading, Management Right.